Ethnic discrimination during wartime: Evidence from a field experiment in the Finnish housing market - Mourelatos Evangelos; Oikarinen Elias (Elsevier Inc., 2025)
This paper presents a field experiment studying possible discrimination against Russians in the rental housing market in Finland. We study the effect of discriminatory behaviour by the landlords during the Russian war of aggression in Ukraine, an event that has shaped ideas, attitudes, and behaviour. We let three fictitious individuals, one Finnish, one Russian and one British, apply for vacant rental apartments advertised by landlords on the internet. We then investigated whether there were differences between the individuals in the number of callbacks received and positive invitations to further contact. Linear probability models revealed strong evidence of differential treatment of Russians by Finnish landlords. The discriminatory behaviour is mainly driven by male, private landlords. The present study extends the literature on discrimination in the rental housing market and provides insights into its mechanisms.